Pembelajaran Kontruktivistik Berbasis Literasi Baru dalam Pendidikan Agama Islam - Ummu Kulsum (IAI Darussalam, 2019)
The constructivist learning model is formulated in three problem formulations, 1) What is the new literacy-based contructivist learning model in Islamic Education? 2) What is the concept of transmission from constructive-based learning to new literacy in Islamic Education? 3) What is the strategy for transforming constructivist learning based on new literacy in Islamic Education? The aim is to describe the learning model, and also describe the concept of transmission from learning and analyze the strategies of transformational constructivist learning based on new literacy in Islamic religious education. The method uses the inductive qualitative literature method, to explain the results of several scientific works then reduced to a finding by developing existing findings into an innovation and invasion for the development of Islamic religious education. The findings are in the form of PAI learning strategies using constructivistic learning models and new literacy theories that produce reflection meta-cognition for students. Constuctivistic learning needs to be developed also in the affective domain in order to be able to provide changes in the character of students so that students feel a change in him every PAI subject matter is given to him.